The modelling of oxide film entrainment in casting systems using computational modelling - Reilly, C.; Green, N. R.; Jolly, Mark R.; Gebelin, J. C. (Elsevier, 2013)
As Campbell stated in 2006, “the use of entrainment models to optimise filling systems designs for castings has huge commercial potential that has so far being neglected by modellers”. In this paper a methodology using computational modelling to define entraining events and track the entrained oxide films is presented. Research has shown that these oxide films present within the casting volume are highly detrimental to casting integrity, thus their entrainment during mould filling is especially undesirable. The method developed for the modelling of oxide entrainment has been validated against previously published data by Green and Campbell (1994) [31]. The validation shows good quantitative correlation with experimental data. However there is scope for further development which has the potential to both improve the accuracy and further validate the technique.
Keywords: Modelling; Oxide films; Casting; Defects; Entrainment; Optimisation